A colorimetric assay for Hg2+ detection based on Hg2+-induced hybridization chain reactions. Issue 35 (21st August 2017) - Wang, Li-Juan; Jia, Li-Ping; Ma, Rong-Na; Jia, Wen-Li; Wang, Huai-Sheng
Abstract : A simple colorimetric sensing method for the detection of Hg 2+ was developed by combining enzymatic catalysis with DNA-based hybridization chain reactions (HCRs). Abstract : A simple colorimetric sensing method for the detection of Hg 2+ was developed by combining enzymatic catalysis with DNA-based hybridization chain reactions (HCRs). Firstly, thymine (T)-rich capture DNA ( c DNA) was immobilized on a gold electrode via Au–S bonding. In the presence of Hg 2+, thymine (T)-rich probe DNA ( p DNA) hybridized with c DNA via T–Hg 2+ –T base pairs. Then the HCRs were realized using p DNA as an initiator and two biotin-labeled hairpin DNAs (H1 and H2) as fuel strands. Finally, numerous avidin-labeled horseradish peroxidase (HRP) enzymes were immobilized on long nicked ds-DNA strands, which can catalyze the H2 O2 -mediated oxidation of 3, 3, 5, 5-tetramethylbenzidine dihydrochloride hydrate (TMB) to cause a dramatic color change. Under optimal conditions, the absorbance of TMB was linear with the logarithm of Hg 2+ concentrations in the range of 1 fM to 1 pM, with a detection limit of 0.33 fM. This strategy exhibited good selectivity and high sensitivity, which might be a potential tool for the practical detection of Hg 2+ in environmental monitoring.